ANALISIS PENGARUH MUTU LAYANAN TERHADAP KEPUASAN PEMOHON SKCK DI POLRES SIDRAP - Lukman Hi Husen; Jamaluddin Ahmad; Ahmad Mustanir (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
This study aims to: 1) analyze the influence of service quality provided by the Sidrap Police Department on the satisfaction of SKCK (Police Record Certificate) applicants; 2) analyze the service quality factors that most dominantly influence the level of satisfaction of SKCK applicants at the Sidrap Police Department; 3) analyze the obstacles faced in maintaining service quality during the SKCK application process at the Sidrap Police Department, and how to overcome them to improve applicant satisfaction. This is a quantitative study conducted at the Sidrap Police Department. The study was designed using a descriptive and explanatory quantitative research design. The population of this study was all Police Record Certificate (SKCK) applicants who applied for SKCKs at the Sidrap Police Department between January 2024 and October 2025. The study sample was drawn at 20%. Data collection techniques used were questionnaires, interviews, and documentation. The collected data were then analyzed using descriptive analysis and validity and reliability tests. The results of this study indicate that: 1) The quality of service provided by the Sidrap Police has a significant influence on the satisfaction of SKCK applicants. Based on an analysis of five dimensions of service quality—reliability, responsiveness, assurance, empathy, and physical evidence—all aspects obtained an average score above 4.0, indicating a high level of satisfaction. 2) The most dominant factors influencing SKCK applicant satisfaction at the Sidrap Police are the friendly and attentive attitude of officers, as well as their alertness and quick response. 3) SKCK processing services at the Sidrap Police still face various obstacles that affect service quality and applicant satisfaction. The main obstacles include long queues, unclear information, limited human resources, technical problems, and a lack of adequate physical facilities.